TESIS BRAND COMMUNITY SEBAGAI UPAYA MENDORONG BRAND AWARENESS DJARUM BLACK (Studi Tentang Black Car Community di Yogyakarta) - , Esti Windarti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Data of Department of Health, which is got from WHO, show Indonesia is a country with the biggest cigarette consumer after China and Indian. On the other side, government feels has the responsibility to look out over the society health. Government makes policy which put more pressure to cigarette producers. Besides government, more creative competitor makes this industrial rivalry more interesting to be studied. Paradox between government, competitor and consumer makes cigarette producers should choose marketing strategy which not break the law yet leave an impression at the consumerâs mind. One of strategies used is making a community or often called with brand community. Brand community is one of strategies used by company aimed consumer always aware towards the product.